Assessing impacts of animal health interventions on productivity - Rowlands, G.J. (1994)
Tsetse control is often applied to an area which covers several herds. To carry out a trial using an uncontrolled area would be difficult because of the virtual impossibility of findings two areas identical in every respect. One solution (method 1) is to compare animal productivity before and after an intervention has been applied, but this requires several years of data to be collected. An alternative method (method 2) is to determine the association to predict the potential outcome should an intervention be applied. A third solution (method 3) which has considerable statistical advantages over the first two, is to utilise herd-to-herd variations in the "primary impact" of the intervention, like on reduction in trypanosome prevalence, to investigate "secondary impacts" on productivity. This approach uses linear regression analysis with herd as the experimental unit, increase in animal productivity resulting from the intervention as the dependent variable and decrease in desease prevalence as the independent variable.